Unilateral elongated styloid process: a case report - Paraskevas, George K (BioMed Central, 2009)
An unusual case of a unilaterally elongated styloid process with a length of 5.8 cm was found on a dry skull of a male cadaver. During his life the subject was complaining for reported ipsilateral otalgia presumably due to nerve compression from the elongated styloid process. The symptomatology appeared by such an anatomical variant as well as relative literature is discussed in this paper.